Nanomembrane-based Apheresis as Safe and Effective Therapy for Cytomegalovirus and Epstein-Barr Virus Reactivation - Slavic, Vjeroslava; Djurdjic, Beti; Randjelovic, Danijela; Rajovic, Gordana; Delic, Marina (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Heavy training schedules or endurance competitions in marathon are forms of extreme physical stress and lead to immunodepression in runners which could be associated with increased susceptibility to viral reactivation by ubiquitous viral infection such as cytomegalovirus (CMV) and Epstein-Barr virus (EBV). Lately, it was confirmed presence of elevated CMV and EBV loads and the lower antibody titers in competitive athletes. The most common clinical features are fatigue and adynamia accompanied with liver damage, varying from mild and transient elevation of aminotransferases to serious acute hepatitis and liver failure. CASE REPORT: Bearing in mind that a professional practice of marathon running is hazardous for the liver, therapeutic action is necessary as soon as possible to avoid serious complications and even cessation of professional competition. In our case report of professional female marathon runner, we need to treat CMV and EBV reactivation which caused liver damage, prevented regular trainings, and upcoming competitions. We opted for four sessions of nanomembrane based apheresis performed every other day for removal pathological products resulting from virus reactivation to break through the course of the disease and to prevent complications. After completing the whole procedure control laboratory tests and abdominal ultrasound were in physiological ranges. CONCLUSION: Hence, nanomembrane based apheresis can be effective and safe treatment of liver damages for elite marathon runners as well as for athletes.